Effects of Chowiseungcheng-tang Extracts on the Preadipocytes Proliferation in 3T3-L1 cell line, Lipolysis of Adipocytes in rat, and Localized Fat Accumulation by extraction methods - Jae-eun, Lee; Byoung Woo, Kim; Ki Rok, Kwon; Tae Jin, Rhim; Dong Heui Kim (Korean Pharmacopuncture Institute, 2008)
Objectives : The purpose of this study is to investigate the effects of Chowiseungcheng-tang extracts on the preadipocytes proliferation in 3T3-L1 cell line, lipolysis of adipocytes in rat's epididymal adipocytes and localized fat accumulation of porcine by extraction methods(alcohol and water). Methods : Diminish preadipocytes proliferation and promote lipolysis of adipocytes do primary role to reduce obesity. So, we used 3T3-L1 mouse embryo fibroblasts(preadipocytes) and rat epididymal adipocytes from Sprague-Dawley rats to investigate the effects of Chowiseungcheng-tang extracts on the preadipocytes proliferation, lipolysis of adipocytes. They were treated with 0.01, 0.1, 1.0㎎/㎖ Chowiseungcheng-tang alcohol and water extracts. And for the purpose of investigating the effects of Chowiseungcheng-tang alcohol and water extracts on the localized fat accumulation, we injected 0.1, 1.0, 10.0㎎/㎖ Chowiseungcheng-tang extracts to porcine fat tissues and observed histological changes of them. Results : Following results were obtained from the preadipocytes proliferation and lipolysis of adipocytes and histological investigation of fat tissues. 1. Chowiseungcheng-tang extracts suppressed preadipocytes proliferation on the high dosage(especially 1.0㎎/㎖), and especially alcohol extracts had better effects. 2. The alcohol extracts of Chowiseungcheng-tang decreased the activity of glycerol-3-phosphate dehydrogenase(GPDH) on the concentrations of 0.1, 1.0㎎/㎖. Alcohol extracts had better effects than water extracts. 3. Chowiseungcheng-tang extracts increased lipolysis of adipocytes on the concentrations of 0.1, 1.0㎎/㎖, and especially on the concentration of 1.0㎎/㎖ alcohol extract of Chowiseungcheng-tang had better effect. 4. The water extract of Chowiseungcheng-tang had significant activity to the destruction of porcine fat cell membranes only on the concentration of 10.0㎎/㎖, but alcohol extracts of Chowiseungcheng-tang had it on all concentrations. Conclusions : The alcohol extracts of Chowiseungcheng-tang had much better effects on the preadipocytes proliferation, lipolysis of adipocytes and localized fat accumulation than water extracts